Counseling criminal justice offenders - Masters, Ruth (Sage Publications, 2004)
Understanding criminal justice counseling -- Criminal justice counseling process -- The role and importance of emotions in counseling criminal justice offenders -- Counseling and the criminal justice offender -- Counseling male and female criminal justice offenders.